Capital Structure, Profitability, and Block Holder Ownership on Dividend Policy using Free Cash Flow as Moderation Variable - Renaldo, Nicholas; Sally; Musa, Sulaiman; Wahid, Nabila; Cecilia (Journal of Applied Business and Technology, 2023)
The aim of this study is to investigate the influence of sales growth, company size, profitability, and non-debt tax shield on the capital structure of food and beverage companies in the consumer sector listed on the Indonesia Stock Exchange between 2017 and 2020. The research utilizes secondary data and employs purposive sampling to select a sample of 38 companies. Data analysis involves quantitative descriptive analysis and the use of SmartPLS software for various calculations. The findings indicate that block holder ownership does not significantly affect dividend policy, capital structure does not significantly impact dividend policy, profitability has a positive influence on dividend policy, and free cash flow does not significantly affect dividend policy. It is hoped that future researchers can add knowledge and insight in the field of financial and financing ratios and examine more deeply related to financial performance in the development of primary consumer goods sector companies on the IDX.